2015
DOI: 10.1515/revneuro-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury: overview of experimental approaches used to restore locomotor activity

Abstract: AbstractSpinal cord injury affects more than 2.5 million people worldwide and can lead to paraplegia and quadriplegia. Anatomical discontinuity in the spinal cord results in disruption of the impulse conduction that causes temporary or permanent changes in the cord’s normal functions. Although axonal regeneration is limited, damage to the spinal cord is often accompanied by spontaneous plasticity and axon regeneration that help improve sensory and motor skills. The recovery pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 83 publications
(111 reference statements)
1
51
0
3
Order By: Relevance
“…Spinal cord injury (SCI), one of the most severe injuries, causes the death of many kinds of cells such as neurons, oligodendrocytes, and astrocytes, in which extensive loss of sensory and motor functions occurs below the injury site [1]. Two different mechanisms have been proposed for the pathogenesis of SCI: a primary mechanical injury and a secondary injury induced by multiple biological processes, including ongoing apoptosis, inflammation, excitotoxicity, and extensive demyelination of axons [1, 2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal cord injury (SCI), one of the most severe injuries, causes the death of many kinds of cells such as neurons, oligodendrocytes, and astrocytes, in which extensive loss of sensory and motor functions occurs below the injury site [1]. Two different mechanisms have been proposed for the pathogenesis of SCI: a primary mechanical injury and a secondary injury induced by multiple biological processes, including ongoing apoptosis, inflammation, excitotoxicity, and extensive demyelination of axons [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…Two different mechanisms have been proposed for the pathogenesis of SCI: a primary mechanical injury and a secondary injury induced by multiple biological processes, including ongoing apoptosis, inflammation, excitotoxicity, and extensive demyelination of axons [1, 2]. Prior studies have suggested that, unlike the peripheral nervous system (PNS), the adult mammalian central nervous system (CNS) has limited axon regeneration ability after SCI, predominantly due to the inability of neurons to regenerate axons through the inhibitory milieu of the glial scar and injured spinal cord lesion [3], which impede the functional recovery after trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a devastating event that can lead to neurological de cits and motor dysfunction [1][2]. The dysfunction of motor and sensory functions after SCI is caused by the following two processes: primary injury and secondary injury.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) causes a high rate of morbidity and disability. Presently, more than 2.5 million people suffer from SCI, with annually reported new cases being about 12,000 in the United States [ 1 , 2 ]. SCI is classified into primary and secondary phases.…”
Section: Introductionmentioning
confidence: 99%